Steam Microturbines in Distributed Cogeneration - Kiciński, Jan; Żywica, Grzegorz (Springer International Publishing : Imprint: Springer, 2014)
This book presents the most recent trends and concepts in power engineering, especially with regard to prosumer and civic energy generation. In so doing, it draws widely on his experience gained during the development of steam microturbines for use in small combined heat and power stations based on the organic Rankine cycle (CHP-ORC). Major issues concerning the dynamic properties of mechanical systems, in particular rotating systems, are discussed, and the results obtained when using unconventional bearing systems, presented. Modeling and analysis of radial-flow and axial-flow microturbines are addressed in detail, covering rotor analysis with different bearing systems, simulation modal analysis, and stress analysis. Furthermore, experimental studies of the dynamic properties of microturbine elements are extensively described. Interest in distributed generation and CHP-ORC is growing rapidly, and the potential market for such systems promises to be very large. This book will be of value for engineers and scientists involved in the design, modeling, operation, and diagnostics of various types of turbomachinery, especially steam microturbines.